2023
DOI: 10.1039/d3ra03168c
|View full text |Cite
|
Sign up to set email alerts
|

Epsilon-poly-l-lysine conjugated erythromycin for enhanced antibiotic therapy

Abstract: Erythromycin was conjugated to ε-poly-l-lysine (EPL) for enhanced antibiotic therapy while not bringing hemolysis and cytotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…ε-PL and nisin A have synergistic antibacterial effects on gram positive foodborne pathogens such as Bacillus cereus and Listeria monocytogenes [34]. Additionally, ε-PL coupled with erythromycin demonstrated relatively strong antibacterial activity against Staphylococcus aureus and Enterococcus faecalis, compared with the ε-PL alone [35]. In this study, an innovative combination of ε-PL, FP and domiphen was developed and its superior antibacterial effect was proved.…”
Section: Discussionmentioning
confidence: 94%
“…ε-PL and nisin A have synergistic antibacterial effects on gram positive foodborne pathogens such as Bacillus cereus and Listeria monocytogenes [34]. Additionally, ε-PL coupled with erythromycin demonstrated relatively strong antibacterial activity against Staphylococcus aureus and Enterococcus faecalis, compared with the ε-PL alone [35]. In this study, an innovative combination of ε-PL, FP and domiphen was developed and its superior antibacterial effect was proved.…”
Section: Discussionmentioning
confidence: 94%
“…Expanding beyond β-lactam antibiotics, Yu et al demonstrated an enhanced antimicrobial ability of EPL-conjugated erythromycin compared to erythromycin alone. 35 This provides evidence to extend the conjugation strategy to more kinds of antibiotics, especially those with a poor or diminishing efficiency. However, with the limitation of this work, further investigation is needed to assess their properties against MDR pathogens and in vivo.…”
Section: Prospects For the Epl−β-lactam Antibiotic Covalent Conjugatesmentioning
confidence: 99%
“…33 In spite of these, limited research has explored the combinations and conjugations of EPL with other antibiotics. 34,35 Among conventional antibiotics, β-lactam antibiotics remain a preferred choice for empiric use due to a low required concentrations. 4 However, their great potential to induce drug resistance and poor synergy with several types of peptides constrain their broader utility.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation